PENGARUH PENDIDIKAN KESEHATAN TERHADAP SIKAP MASYARAKAT KEPADA SUSPECT COVID-19 DIDUSUN AUR KUNING - Achmad Vindo Galaresa, Heri Syahriansyah (Jurnal Ilmiah Keperawatan, 2021)
Background: Corona virus or severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a virus that attacks the respiratory system, a disease due to viral infection is called covid-19. The number of positive cases of Covid-19 increased by 399 cases, bringing the total to 4,241 to 12 April 2020. Purpose: to determine the effect of health education on public attitudes towards Covid-19 suspect in Aur kuning village. Methods: The research design used was pre-experimental with a one group pretest-posttest design approach. The sample size was 150 respondent in Aur Kuning village, Pebenaan village, Keritang district, Indragiri Hilir regency, Riau, using total sampling. Results: The results of the study were based on the Wilcoxon test where the p value <0.025 was smaller than the alpha value (p <0.05). Conclusion: health education about covid - 19 had an influence on the attitudes of the community in Aur Kuning village.